Comparing recombinant human rabies monoclonal antibody (ormutivimab) with human rabies immunoglobulin (HRIG) for postexposure prophylaxis: A phase III, randomized, double-blind, non-inferiority trial - Xiaoqiang Liu; Yufeng Li; Jingyu Li; Jianmei Zhou; Jiangshu Guo; Yi Pu; Ya Jiang; Yaling Zhou; Zhiwei Jiang; Qun Shu; Cha Wang; Jingke Wang; et al. (International Journal of Infectious Diseases, 2023)
Objectives: To evaluate the immunogenicity and safety of an anti-rabies monoclonal antibody (mAb), ormutivimab, compared with human rabies immunoglobulin (HRIG). Methods: This phase III trial was designed as a randomized, double-blind, non-inferiority clinical trial in patients aged ≥18 years with suspected World Health Organization category Ⅲ rabies exposure. The participants were randomized 1:1 to ormutivimab and HRIG groups. After thorough wound washing and injection of ormutivimab/HRIG on day 0, the vaccination was administered on days 0, 3, 7, 14, and 28. The primary endpoint was the adjusted geometric mean concentration (GMC) of rabies virus-neutralizing activity (RVNA) on day 7. The endpoint of safety included the occurrence of adverse reactions and serious adverse events. Results: A total of 720 participants were recruited. The adjusted-GMC of RVNA (0.41 IU/ml) on day 7 in ormutivimab group was not inferior to that in the HRIG group (0.41 IU/ml), with ratio of adjusted-GMC of 1.01 (95% confidence interval: 0.91, 1.14). The seroconversion rate of the ormutivimab group was higher than that of the HRIG group on days 7, 14, and 42. Most local injection sites and systemic adverse reactions reported from both groups were mild to moderate in severity. Conclusion: ormutivimab + vaccine can protect victims aged ≥18 years with category Ⅲ suspected rabies exposure as a component of postexposure prophylaxis. ormutivimab has a weaker influence on the immunity response of rabies vaccines. Clinical trials registration: ChiCTR1900021478 (the Chinese Clinical Trial Registry of World Health Organization).